Under-5 Mortality in Tanzania: A Demographic Scenario - Sathiya Susuman, A (Tehran University of Medical Sciences, 2012)
BACKGROUND: The government of the United Republic of Tanzania has initiated the Integrated Management of Childhood Illness program to improve the health and wellbeing of children. METHODS: Tanzania’s under-five mortality rate is still 1.7 times higher than the world average and, in order to achieve its Millennium Development Goal 4 target, its annual reduction rate is quite low at 2.2. The main aim of the study is to examine under-five mortality combined with the Data from the Tanzania Demographic and Health Survey 2008 data was used. Odds ratios for infant and under-five mortality were estimated using logistic regression; crude and adjusting models were adopted. RESULTS: Mortality cases (18.3%) have been reported to children born with an interval of <24 months. Mothers with no education reported 14.6%, primary education mothers reported 11.1% and higher education reported only 5.3% (P<0.001). Therefore, maternal education plays is a major role on fertility and infant and under-five mortality behavior. CONCLUSION: Maternal education also influences a mother’s behavior in her usage of available health services to improve the health of the children. Further in-depth analysis is immensely needed in this situation.